Revealing Donor–Acceptor Interaction on the Printed Active Layer Morphology and the Formation Kinetics for Nonfullerene Organic Solar Cells at Ambient Conditions. Issue 14 (27th February 2022) - Jiang, Xinyu; Chotard, Pauline; Luo, Kexun; Eckmann, Felix; Tu, Suo; Reus, Manuel A.; Yin, Shanshan; Reitenbach, Julija; Weindl, Christian L.; Schwartzkopf, Matthias; Roth, Stephan V.; Müller‐Buschbaum, Peter
Abstract: Slot‐die coating is a powerful method for upscaling the production of organic solar cells (OSCs) with low energy consumption print processes at ambient conditions. Herein, chlorobenzene (CB) and chloroform (CF) are compared as host solvents for printing films of the neat novel fused‐ring unit based wide‐bandgap donor polymer (PDTBT2T‐FTBDT), the small molecule nonfullerene acceptor based on a fused ring with a benzothiadiazole core (BTP‐4F) as well as the respective PDTBT2T‐FTBDT:BTP‐4F blend films at room temperature in air. Using CF printing of the PDTBT2T‐FTBDT:BTP‐4F active layer, OSCs with a high power conversion efficiency of up to 13.2% are reached in ambient conditions. In comparison to CB printed blend films, the active layer printed out of CF has a superior morphology, a smoother film surface and a more pronounced face‐on orientation of the crystallites, which altogether result in an enhanced exciton dissociation, a superior charge transport, and suppressed nonradiative charge carrier recombination. Based on in situ studies of the slot‐die coating process of PDTBT2T‐FTBDT, BTP‐4F, and PDTBT2T‐FTBDT:BTP‐4F films, the details of the film formation kinetics are clarified, which cause the superior behavior for CF compared to CB printing due to balancing the aggregation and crystallization of donor and acceptor. Abstract : The printing of active layers for nonfullerene organic solar cells is studied at ambient conditions with in situ techniques to rationalize why the best performing devices are achieved with printing out of chloroform in terms of morphology and crystal structure.